Termination of Pregnancy for Medical Indications under Sec. 218a Para. 2 of the German Criminal Code – Real-life Data from the “Gießen Model” - Dettmeyer, Reinhard; Lang, Juliane; Axt-Fliedner, Roland; Birngruber, Christoph; Tinneberg, Hans-Rudolf; Degenhardt, Jan (Geburtshilfe und Frauenheilkunde, 2017)
Background Following the legal provisions on the termination of pregnancies in Art. 13 of the SFHG (Law on the Assistance for Pregnant Women and Families, passed on 27.07.1992, BGBl. I, p. 1398) the so-called embryopathic indication for termination was abandoned. Since then, sec. 218a para. 2 of the German Criminal Code (StGB) states that for late terminations, i.e., terminations after the 12th week of gestation post conception, the pregnant woman must be in exceptional distress “according to medical opinion”. Method Between 01.05.2012 and 25.07.2016, a total of 160 pregnancy terminations were carried out in Gießen University Hospital under sec. 218a para. 2 StGB. The following data were obtained from the patientsʼ files: age of the pregnant woman, number of pregnancies, type of fetal disease or malformation, time of diagnosis, medical and psychosocial counseling given to the pregnant woman, time of termination or delivery, type of termination, fetal gender. Results 160 pregnant women (mean age: 31.6 years) underwent termination of pregnancy between the 13th – 37th week of gestation. Chromosomal anomalies were diagnosed prenatally in 60 cases, and anomalies were diagnosed on ultrasonography in 100 cases, with the preponderance of cases presenting with developmental disorders of the central nervous system and cardiovascular system. Conclusion In addition to recording intrauterine fetal disorders, when pregnancies are terminated under sec. 218a para. 2 StGB, treating physicians are expected to give plausible reasons why “according to medical opinion” the pregnancy represents a danger to the life of the pregnant woman or of grave injury to her physical or mental health and enter these reasons in the patientʼs medical records.Hintergrund Mit der gesetzlichen Regelung des Schwangerschaftsabbruchs durch Art. 13 des SFHG (Schwangeren- und Familienhilfegesetz vom 27.07.1992, BGBl. I, S. 1398) wurde die sog. embryopathische Indikation verlassen. § 218a Abs. 2 StGB verlangt seither für einen sog. Spätabbruch nach der 12. SSW p. c. eine „nach ärztlicher Erkenntnis“ gegebene Notlage der Schwangeren. Methodik Vom 01.05.2012 bis zum 25.07.2016 wurden im Universitätsklinikum Gießen 160 Schwangerschaftsabbrüche gem. § 218a Abs. 2 StGB vorgenommen. Den Krankenunterlagen wurden folgende Daten entnommen: Alter der Schwangeren, Zahl der Schwangerschaften, Art der Erkrankungen des Feten, Zeitpunkt der Diagnose, medizinische und psychosoziale Beratung der Schwangeren, Zeitpunkt des Spätabbruchs und der Entbindung, Art des Schwangerschaftsabbruchs, Geschlecht des Feten. Ergebnisse Bei 160 Schwangeren, Durchschnittsalter 31,6 Jahre, wurde in der 13.–37. SSW die Schwangerschaft abgebrochen. In 60 Fällen waren pränatal chromosomale Anomalien diagnostiziert worden, in 100 Fällen wurden sonografisch Anomalien mit dominierenden Entwicklungsstörungen des ZNS und des kardiovaskulären Systems diagnostiziert. Schlussfolgerung Neben der Dokumentation der intrauterinen Erkrankung des Feten wird beim Schwangerschaftsabbruch gem. § 218a Abs. 2 StGB von den behandelnden Ärzten erwartet, dass die „nach ärztlicher Erkenntnis“ gegebene Gefahr für das Leben oder die Gefahr einer schwerwiegenden Beeinträchtigung des körperlichen oder seelischen Gesundheitszustands der Schwangeren in den Krankenunterlagen plausibel dargelegt wird.
Keywords: termination of pregnancy; feticide; legal requirements